Superalloys 2016 2016
DOI: 10.1002/9781119075646.ch93
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residual Stresses on the Fatigue Life of a Shot‐Peened Nickel‐Based Single Crystal Superalloy: From Measurements to Modeling

Abstract: In this work, X-ray diffraction measurements and finite elements calculations are combined to investigate the effect of the shot-peening process on the fatigue lifetime of the AMI nickel-based single crystal superalloy. The Ortner method is used to determine residual elastic stress depth profiles in plane-parallel samples. They exhibit a I30-I60 µm thick hardened layer where there are compressive stresses up to 1000-I400 MPa. The tensile stresses which ensure the mechanical equilibrium of the samples are not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several researchers reported the influence of residual stresses and its stability on fatigue performance of materials. [10][11][12][13] For example, Doremus et al 14 reported that residual stresses delay the crack growth during the first stage of propagation as compared to long crack growth indent type surface anomalies and also affect the crack front shape. Dalaei et al 15 reported that a significant improvement in fatigue life can be expected as long as surface residual stresses are higher than the 50% of stress amplitude at half of the lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers reported the influence of residual stresses and its stability on fatigue performance of materials. [10][11][12][13] For example, Doremus et al 14 reported that residual stresses delay the crack growth during the first stage of propagation as compared to long crack growth indent type surface anomalies and also affect the crack front shape. Dalaei et al 15 reported that a significant improvement in fatigue life can be expected as long as surface residual stresses are higher than the 50% of stress amplitude at half of the lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers reported the influence of residual stresses and its stability on fatigue performance of materials 10–13 . For example, Doremus et al 14 reported that residual stresses delay the crack growth during the first stage of propagation as compared to long crack growth indent type surface anomalies and also affect the crack front shape.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is consistent with the observation of the anomalous rafting in this zone. Amélie Morançais et al [19] researched the effect of shot-peening on the low-cycle fatigue life of AM1 superalloy by XRD. Compressive stresses of up to 1000-1400 MPa were found on the surface layer by XRD.…”
Section: Introductionmentioning
confidence: 99%